Sining biswal [videorecording] a documentary on Philippine visual arts (Tuklas sining series, 1989)
Highlights the many paths that the Filipino visual artists have explored in their quest for identity. These include the indigenous bulol, manunggul jar, t'nalak and T'boli textiles; altars and santos of the Spanish colonial period; rural landscapes and other paintings of the American period; and modernist, neo-realist, expressionist and social realist schools of contemporary times.